Ectopic Cushing’s Syndrome From Prostatic Adenocarcinoma: A Rare Clinical Entity (Journal of Chittagong Medical College Teachers' Association, 2020)
A 61-year-old man known to have metastatic prostate adenocarcinoma was seen at Changi General Hospital, Singapore, because of severe hypokalaemia due to ACTH dependent Cushing’s syndrome. He underwent a Dotate PET CT which showed increased DOTA-NOC-avidity in the right side of the prostate gland. Subsequent immunohistochemical staining of prostate biopsy sample documented ACTH, synaptophysin and CD 56 positivity. He was suggested medical management for prostate cancer complicated by Cushing's syndrome. Unfortunately, Cushing’s syndrome was not controlled and the patient’s clinical condition progressively worsened. Subsequently, he developed fatal sepsis due to immunocompromised state. This case report describes a case of Cushing’s syndrome due to metastatic adenocarcinoma of the prostate, a tumour with very few therapeutic options and negative prognosis.JCMCTA 2020 ; 31 (1) : 125-129